Type III Osteogenesis Imperfecta with Severe Limb Deformities: A Report with Review of The Literature - Zacharia, Balaji; Kambagi, Kashinath Yamanappa; Kumar, R. Manoj ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2025)
Background: Type III osteogenesis imperfecta (OI) is very rare. In this article, we describe the clinical features and management of a case of type III osteogenesis imperfecta with a review of the literature.Case Report: A 5 – year - old girl presented with deformities of the bilateral lower and upper limbs. Posterior bowing of both humerus, cubitus varus deformity of both elbows, shepherd crook deformities of the femur, and anterolateral bowing of both legs were observed. She was unable to walk. Her face was triangular, and she had a kyphoscoliotic deformity of the spine. Radiographs showed osteopenia and multiple fractures at different stages of healing. The clinical and radiological findings were consistent with those of type III OI. She was treated by deformity correction of the right femur and tibia using the Sofield technique.Discussion: OI is a disorder caused by a mutation in type 1 collagen. It is characterized by increased bone fragility, dentigerous imperfecta, and generalized ligamentous laxity. There are 18 types of OI. We describe a case of type 3 OI in which the child developed deformity of the spine and limb at a later age without involvement of the sclera. Lower limb deformities were corrected using the Sofield technique of multiple osteotomies and intramedullary nailing. The implants were removed once the osteotomies were united. After implant removal, anterolateral bowing of the tibiae recurred.Conclusions: Long bone deformities can be managed using the Sofield technique. Long-term follow-up is essential for the early detection and correction of recurrence.